Treasure Hunter Game Buah Maja Menggunakan Scirra Construct 2 - Ade Bastian; Dadan Zaliluddin; Devi Sukrisna (Universitas PGRI Kanjuruhan Malang, 2019)
Majalengka is one of the regencies located in West Java Province. With the diversity of cultures and tourist attractions in Majalengka, the author intends to make a game that can accommodate several aspects of Majalengka so that it can be better recognized by the public, especially the Majalengka community itself. This research aims to introduce Majalengka to the outside community and the Majalengka community itself, through Majalengka icons and their natural wealth in the form of legendary Gincu and Maja Fruit. The system development method used is a development method using the MDLC (Multimedia Development Life Cycle) method. Questionnaires were given to people who had tried playing the Treasure Hunter Buah Maja, a questionnaire was made aimed at finding out the people's response to the game. With a result of 77.5%, the community stated when they first tried the application to be easy to use. 80.8% of the people expressed interest in using the Treasure Hunter Buah Maja game. And as much as 85% of the people stated that this game was quite entertaining.